The Nexus between Environmental Corporate Social Responsibility Disclosure and Firm Performance in Pakistan - Mehak Zara; Faiza Saleem (Journal of Business & Tourism, 2023)
The corporate social responsibility (CS_R) is considered a key factor in the realm of finance and is regarded as an important aspect of investment decision-making. This research aims to look into the impact of the environmental dimension of CS_R disclosure on firm financial performance (F-P) in the Banking sector of Pakistan. This study utilizes secondary quantitative data gathered from published annual reports of publicly traded banks and the official website of the Pakistan Stock Exchange (PSX) from 2010 to 2020. The study applied the fixed effect model (F-E-M) or a random effect model (R-E-M) for analysis purposes, along with some pre-requisite diagnostic tests. The independent variable of the study is the environmental dimension of CS_R, while the dependent variable of the study is firm F-P proxied by return on assets (R-O-A) and return on equity (R-O-E) respectively. Control factors such as business size and debt ratio were also employed in the study. The outcome of the study showed that there is a significant relationship between environmental CS_R and F-P in Pakistan's banking industry. This particular research assists companies in understanding the significance of CS_R disclosure in improving the financial performance of the banking industry. The study's conclusions should have practical applications for firms, governments, financial advisors, and Pakistan's banking industry.